The Impact Of Service Quality On The Loyalty Of Patients Referring To Outpatient Clinics Of Studied Hospitals In Tehran - Seyed jamalodin Tabibi; Mahmud Reza Gohari; Mohammad Sabahi Bidgoli; Somayeh Shahri (Tehran University of Medical Sciences, 2012)
Background and Aim: The present case study aims to investigate the impact of service quality on patients' loyalty to the services rendered in outpatient clinics of the studied hospitals throughout Tehran. Materials and Methods: This is a descriptive-analytical survey in which 242 outpatients referring to the studied hospital clinics in Tehran. For data collection purposes, the standardized SERVQUAL questionnaire(1988) and for the measurement of loyalty for service quality, the standard questionnaire for customer's behavioral tendencies(Zitamel and Berry, 1996) were used. Regarding the validity of the questionnaire, its content validity was confirmed and its reliability was approved through test-retest method and Cronbach's alpha coefficient. For data analysis, Pearson correlation test was employed. Results: The results revealed that there was a positive and meaningful relationship between the quality of services and the patients' loyalty in Tehran clinics. The most important aspect of loyalty was complaining behavior. Conclusion: Hospital managers should enhance their understanding and awareness to maintain, and even improve, the patients' loyalty to their services and should do their best in this regard. Hospital employees should be aware of the patients' expectations and act beyond it. Finally, they should know that rendering services to patients is teamwork and that the key to providing patients with good services lies in their satisfaction with the quality of services they receive.